2017
DOI: 10.1016/j.cbpa.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Imine reductases (IREDs)

Abstract: Imine reductases (IREDs) have emerged as a valuable new set of biocatalysts for the asymmetric synthesis of optically active amines. The development of bioinformatics tools and searchable databases has led to the identification of a diverse range of new IRED biocatalysts that have been characterised and employed in different synthetic processes. This review describes the latest developments in the structural and mechanistic aspects of IREDs, together with synthetic applications of these enzymes, and identifies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
161
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(163 citation statements)
references
References 52 publications
1
161
0
1
Order By: Relevance
“…As an alternative to traditional chemical methods, biocatalysis is becoming an increasingly desirable option for industry owing to the benefits of sustainable catalyst supply, milder reaction conditions, and the enantioselectivity offered by enzymes. One of the more recent additions to the suite of biocatalysts available for chiral amine synthesis are imine reductases (IREDs), which catalyze the asymmetric reduction of prochiral imines by using the cofactor NADPH (Figure a) . It has also been shown that, as well as the reduction of preformed imines, certain enzymes of this class can also enable reductive amination between a carbonyl and amine substrate .…”
Section: Figurementioning
confidence: 99%
“…As an alternative to traditional chemical methods, biocatalysis is becoming an increasingly desirable option for industry owing to the benefits of sustainable catalyst supply, milder reaction conditions, and the enantioselectivity offered by enzymes. One of the more recent additions to the suite of biocatalysts available for chiral amine synthesis are imine reductases (IREDs), which catalyze the asymmetric reduction of prochiral imines by using the cofactor NADPH (Figure a) . It has also been shown that, as well as the reduction of preformed imines, certain enzymes of this class can also enable reductive amination between a carbonyl and amine substrate .…”
Section: Figurementioning
confidence: 99%
“…Since then, IREDs have rapidly assumed an important role as highly stereoselective catalysts for amine synthesis. [18][19][20][21][22][23][24] IREDs strictly require NADPH and are preferentially used in cellular systems, which makes them very suitable for application in photosynthesis-driven whole-cell biotransformations.…”
mentioning
confidence: 99%
“…[12] Only ah andful of examples have been reported involving enantioselective transformations with modest enantiomeric excess. [16][17][18][19][20][21][22][23][24] These enzymes have also been combined in cascades to carry out multiple transformations in one pot, often with the oxidation and reduction steps taking place concurrently. [16][17][18][19][20][21][22][23][24] These enzymes have also been combined in cascades to carry out multiple transformations in one pot, often with the oxidation and reduction steps taking place concurrently.…”
mentioning
confidence: 99%